The effect of a natural feed additive, fenugreek, on feed digestibility and milk response in dairy goats - Smit, Hendrik Petrus Jordaan (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScAgric)--Stellenbosch University, 2014.